2007
DOI: 10.1185/030079907x199817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ezetimibe on lipids and lipoproteins in patients with hyper­cholesterolemia and different apolipoprotein E genotypes

Abstract: Ezetimibe significantly improved lipid and lipoprotein profiles from baseline irrespective of apoE epsilon3/epsilon3 or epsilon4 genotype in Hungarian subjects not at cholesterol goals. Limitations of our study include its open-label nature and small sample population, as well as the facts that patients with the epsilon4 allele were not included and data were not collected on initial cholesterol levels, initial statin doses, cholesterol responses to statins, and the safety and tolerability of ezetimibe. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
3
0
4
Order By: Relevance
“…There is only one study concerning the modulating effect of APOE ε2/ε3/ε4 polymorphism during ezetimibe treatment [73]. This open-label study included only 28 patients; no genotyperelated differences were found in the lipid status during the 6-week treatment.…”
Section: Apoe Polymorphisms and The Response During Lipid-lowering Therapymentioning
confidence: 99%
“…There is only one study concerning the modulating effect of APOE ε2/ε3/ε4 polymorphism during ezetimibe treatment [73]. This open-label study included only 28 patients; no genotyperelated differences were found in the lipid status during the 6-week treatment.…”
Section: Apoe Polymorphisms and The Response During Lipid-lowering Therapymentioning
confidence: 99%
“…Pharmacophore detection shared by selected input ligand molecules (Ligand75_24, Ligand75_37, Ligand75_49, Ligand75_76, Ezetimibe drug) was checked by PharmaGist (http://bioinfo3d.cs.tau.ac.il/PharmaGist/) which is a ligand-based method (Schneidman-Duhovny et al, 2008). Ezetimibe, a drug used in the treatment of CAD, shown to have significant improvement in lipid and lipoprotein profile (TC, LDL-C, triglycerides and HDL-C) in patients with APOE3 and APOE4 genotypes (Mark et al, 2007). Pharmacophore mapping of the selected ligands showed shared pharmacophore features between the 4 ligands and the Ezetimibe drug, containing 2 hydrophobic contacts and 2 hydrogen bond donors as shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacophore detection shared by selected input ligand molecules (Ligand75_24, Ligand75_37, Ligand75_49, Ligand75_76, Ezetimibe drug) was checked by PharmaGist (http://bioinfo3d.cs.tau.ac.il/PharmaGist/) which is a ligandbased method [38]. Ezetimibe, a drug used in the treatment of CAD, shown to have significant improvement in lipid and lipoprotein profile (TC, LDL-C, triglycerides and HDL-C) in patients with APOE3 and APOE4 genotypes [39]. Pharmacophore mapping of the selected ligands showed shared pharmacophore features between the 4 ligands and the Ezetimibe drug, containing 2 hydrophobic contacts and 2 hydrogen bond donors as shown in Figure 5.…”
Section: Figure 4 (A): Receptor-ligand Interactions Visualized Using Discovery Studio Showing the Amino Acid Residues Interacting Throughmentioning
confidence: 99%